Emerging Trends in Intimate Partner Rape and Marital/Spousal Rape During the Biennium 2020 and 2021, Including the COVID-19 Pandemic in Greece - Karakasi, Maria-Valeria (Journal of interpersonal violence, 2025)
Intimate partner or marital/spousal rape is a phenomenon with unique characteristics and dynamics. Furthermore, it is an under-explored, under-defined, under-reported, and widely tolerated phenomenon. Gender-based violence and intimate partner violence are the main topics of the present study. The study aimed at exploring the trends in reported intimate partner and marital/spousal rape, within the wider context of reported domestic violence during the years 2020 and 2021 in Greece. Statistical analysis has not indicated positive correlation between the rate of reported domestic violence per year and the rate of reported domestic rape per year, with the former following an upward trend and the latter maintaining an almost steady course. Similarly, the rate of reported victims of intimate partner rape per year remained almost stable within in the 2 years. Importantly however, in 2021, the rate of reported victims of marital rape per year increased remarkably compared to 2020. In 2021, the rates of reported domestic violence per month and reported domestic rape per month indicated remarkable increase over the period May to December 2021. Notwithstanding, the rates mentioned above remained almost stable over the year 2020, showing an upward trend during the summer months. In August 2020 and 2021 the abovementioned rates reached their peak. In both years, the vast majority of victims of domestic rape were females, mostly between 30 and 45 years of age. The present study indicated an increase in rates of reported domestic violence and reported domestic rape per month after the lockdowns, especially after the second long-lasting lockdown that ended in May 2021. This increase, however, might be only apparent. Further research is needed to study the epidemiology of intimate partner and marital rape over a much longer timespan to provide further insight into the dynamics surrounding a public health concern.